2002
DOI: 10.1523/jneurosci.22-20-08785.2002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Nicotinic Receptor Subtypes Expressed on Dopaminergic Terminals in the Rat Striatum

Abstract: Neuronal nicotinic acetylcholine receptors (nAChRs) expressed on mesostriatal dopaminergic neurons are thought to mediate several behavioral effects of nicotine, including locomotion, habit learning, and reinforcement. Using immunoprecipitation and ligand-binding techniques, we have shown that both alpha6beta2* and alpha4(nonalpha6)beta2* nAChRs are expressed in the caudate-putamen and that only alpha6* nAChRs can bind alpha-conotoxin MII and methyllycaconitine with affinities of 1.3 and 40 nm, respectively. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
354
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 365 publications
(386 citation statements)
references
References 26 publications
26
354
1
1
Order By: Relevance
“…These findings from receptor binding studies are in agreement with the results of in situ hybridization and RT-PCR work, which demonstrate the presence of α2 through α7 and β2 through β4 nAChR subunit transcripts in the striatum and/or substantia nigra [72][73][74][75][76][77]. The results of immunoprecipitation studies using subunit-selective nAChR antibodies suggest that the greater majority of these transcripts are translated into protein to form receptors [64,78]. These show that all but the α2, α3 and β4 subunits are present in the striatum and/or substantia nigra of mice and rats.…”
Section: Rodentssupporting
confidence: 87%
See 2 more Smart Citations
“…These findings from receptor binding studies are in agreement with the results of in situ hybridization and RT-PCR work, which demonstrate the presence of α2 through α7 and β2 through β4 nAChR subunit transcripts in the striatum and/or substantia nigra [72][73][74][75][76][77]. The results of immunoprecipitation studies using subunit-selective nAChR antibodies suggest that the greater majority of these transcripts are translated into protein to form receptors [64,78]. These show that all but the α2, α3 and β4 subunits are present in the striatum and/or substantia nigra of mice and rats.…”
Section: Rodentssupporting
confidence: 87%
“…The loss of α6β2* receptors correlates well with declines in the striatal dopamine transporter, a dopaminergic neuronal marker [64,78,108], suggesting that this receptor subtype is located primarily on striatal dopaminergic nerve terminals. The results of immunoprecipitation studies using nAChR subunit-targeted antibodies support these findings and show that the largest reductions are in α6 and β3 subunit proteins, followed by smaller declines in α4, α5 and β2 subunits [64,78]. There was no change in α7 nAChRs, while the α2, α3 and β4 subunit proteins are not expressed in rodent striatum.…”
Section: Rodentsmentioning
confidence: 92%
See 1 more Smart Citation
“…In this study, we identified reduced Chrnα6 expression in ak striata. α6-subunit containing nicotinic receptors are selectively expressed on dopaminergic terminals in the striatum (Wonnacott et al, 2000;Zoli et al, 2002). Therefore, it is possible that reduced Chrnα6 expression reflects a presynaptic striatal alteration due to the failure of dorsal striatonigral afferents to develop in these mice (Nunes et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…These α6* subtypes are, presumably, the nAChRs that bind [ 125 I]-α-CtxMII with high affinity. Comparable studies done with the rat identified α4α5β2, α4α6β2(β3) and α6β2(β3) nAChRs in striatum (the (β3) designation was used to indicate the possible presence of the β3 subunit) [93]. Thus, immunological approaches indicate that a minimum of five nAChR subtypes (α4β2, α4α5β2, α4α6β2β3, α6β2β3 and .…”
mentioning
confidence: 99%